(untitled) (Journal of the College of Education for Women, 2019)
This research in the philosophy of ethics, we have written under the title (Sensory And Mental Dialogue In The Philosophy Of Ethics -Criticism And Analysis-). Consists of three sections; first: talked dealt within the second part; we writhe about controversial consepts of sensory and mental. Then we about the concept of common philosophical doctrines, either in the third section we talked about the concept of the mind doctrines that secured sence mainly studies in philosophy. The purpose for which our finding in this research is to show that undeniable sense or exceeded in any doctrine of mentale doctrines, just as the mind can not be bypassed or undeniable doctrines sensory ... So as to complete the theory that we have in our thesis to obtain post-Doctorate degree in Ethics philosophy. Namely, that the sensory and mental in separable chaper mechanically naive as did most philosophers, and can not be considered as on (sense or mind) represents a certain degree in the other ladder. But the emergence of sensory and mental together as they advances the application together, and thus can understand the true construction of ethics values. And we study examining solid scientific concepts of ethics and rely on the right method.